Experiment investigation of a two-stage thermoelectric cooler under current pulse operation. (15th October 2016) - Lin, Shumin; Ma, Ming; Wang, Jun; Yu, Jianlin
Highlights: An experiment investigation on current pulse driven two-stage TEC is presented. The effects of main operation parameters on the TEC performance are evaluated. The supercooling phenomenon can be achieved by imposing current pulse on the TEC. Abstract: In this paper, the cooling performance of a two-stage thermoelectric module (TTEM) under pulse current operation was experimentally investigated. A commercial module TEC2-25507 was selected as the tested TTEM and a water-cooled heat sink was used. The impacts of main operation parameters on the TTEM cold side temperature were examined, including inlet water temperature and flow rate, pulse current amplitude, pulse current duration and heat load. The experimental results indicated that those parameters significantly affected the transient characteristics of the TTEM cold side temperature, such as the supercooling effect and the temperature overshoot. Especially, the amplitude and the duration of the pulse current play key roles in determining the TTEM cold side temperature. Moreover, when subjected to cyclic pulse currents, the cold side temperature profile during the first pulse current determines those during the subsequent pulse currents. The experimental results obtained in this study can provide a basis for developing TTEM applications under pulse current operations.